Faktor-Faktor Pendukung dan Penghambat Semangat Belajar Siswa: Studi Kasus pada Siswa Kelas XII SMK Mandiri Medan - Harahap, Ade Chita Putri; Anggina, Asih; Ritonga, Dahniar; Amarta, Muhammad Aji; Ayumi, Salshainbila; Rahmi, Wardatur; Mariana, Wina; Nst, Yeni Rahman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The spirit of learning for students is very important to support their academic and non-academic achievements. Student failures are a concern for researchers to see the background that is the source of learning spirit. Based on the research results, many cases make students lose interest in learning because there is no learning spirit from within the students themselves. This study will examine the factors that hinder and support student learning spirit at SMK Mandiri Medan. The method used in this research is qualitative method, with researchers conducting direct observations and interviews with several students as samples. The results of the study show that supporting factors for student learning spirit include high motivation, enthusiasm, sense of achievement, and desire for development. Meanwhile, the obstacles to student learning spirit in class XII of SMK Mandiri Medan include an uncondusive learning environment, lack of support for students, pressure, and excessive demands.